Fabrication of sodium dinitrophenol derived carbon dots and its effect on seed germination of cotton. (16th March 2022) - Han, Shuai; Wang, Jiang; Ren, Yicheng; Yang, Baoxin; Liu, Xiaoyu; Yang, Jiajia; Liu, Lijuan; Meng, Ke; Shan, Wenrong; Qin, Shenjun
Abstract: Sodium dinitrophenol, which was a cheap and common plant growth regulator, was used to fabricate novel carbon dots by a simple and green hydrothermal treatment. The sodium dinitrophenol derived CDs (SCDs) obtained were found to possess good water solubility, excellent stability, and unique fluorescence properties. Furthermore, the effect of SCDs on the seed germination of cotton was explored in dark environment. Interestingly, the SCDs could promote seed germination obviously and the optimum concentration was tested to be 0.02 mg/mL. By the analysis of the contents of free water and bound water for the sprouts, it was assumed that the phenomenon might be attributed to the enhancement of the respiration and metabolism by the addition of SCDs, which helped to relieve seed dormancy and promote germination. This work supplied a novel nanomaterials for seed treatment, which could enhance the respiration during germination and showed considerable prospect in biological technology and farming production.